The relevance of mathematics: The case of functional mathematics for vocational students - Dalby, Diane (2014)
This study of recent school-leavers in Further Education explores students’ opinions of relevance and how these are influenced by their experiences of different mathematics curricula in school and college. These vocational students are taught mathematics as a functional ‘tool for life’ rather than a discipline of rules.